Економска ситуација у свету и нови развојни образац Кине током пандемије ковида 19 - Ding, Yifan (Napredak, 2021)
The COVID pandemic has devastated the world economy, which has also caused serious slumps in Western developed countries. Although they have adopted “ultra-easy” monetary policy, the real economy did not emerge from recessions because of it and a global “liquidity bubble” was caused instead. The economic recession caused by the pandemic in developed countries may last for years. The governments of some countries in the United States and Europe have adopted strong state intervention methods to control the investment and trade behaviors of enterprises, then force them to "decouple" from China. Based on an objective analysis of the current international situation, China has actively taken countermeasures: on the one hand, it emphasizes mainly relying on the “domestic economic cycle” to maintain growth momentum. And on the other hand, it develops an “international economic cycle” that focus on China`s economy. Establishing a “dual circulation” new development pattern, in which domestic economic cycle plays a leading role while international economic cycle remains its extension and supplement, is a major strategic choice for achieving high-quality economic development.